MENCEGAH ESKALASI KONFLIK KEAGAMAAN: - Husni Mubarok (Jurnal Dialog, 2014)
Although religious conflict is one of the most serious problems in Indonesia in the post New Order era, there has been few reports either on mass media or research institutions that offer the data of resolved conflicts. This paper examines an interfaith conflict, Natal Bersama in Ungaran District, Semarang, Central Java in 2012. This paper attempts to explain as to why such a conflict happened and how it was resolved, and what is the implication for taming religious-based conflicts in Indonesia.